2011
DOI: 10.3342/ceo.2011.4.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Double Glomus Tumors Originating in the Submandibular and Parotid Regions

Abstract: Glomus tumors are rare neoplasms that originate from the glomus bodies, an arteriovenous anastomosis with a specialized vascular structure. The most common site for these tumors is the subungal region of the fingers. Occasionally, glomus tumors are found in the middle ear, trachea, nasal cavities, stomach, and lungs. The occurrence in the parotid regions is very rare. While multiple glomus tumors in the whole body are thought to represent only 10% of all cases, instances of multiple tumors in the neck have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Glomus tumors are rare, accounting for fewer than 2% of soft tissue tumors. However, nearly 10% of cases involve multiple lesions [3]. This tumor is most common in the skin or superficial soft tissue, particularly in the subungual region, and can be found in deep soft tissue and internal organs (such as the nerves, bone, penis, bladder, mediastinum, gastrointestinal tract, liver, and cervix) [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glomus tumors are rare, accounting for fewer than 2% of soft tissue tumors. However, nearly 10% of cases involve multiple lesions [3]. This tumor is most common in the skin or superficial soft tissue, particularly in the subungual region, and can be found in deep soft tissue and internal organs (such as the nerves, bone, penis, bladder, mediastinum, gastrointestinal tract, liver, and cervix) [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Glomangiomyoma: this type is the rarest, with an overall structure similar to that of a solid tumor or hemangioma, but with a transition between typical cells and spindle cells resembling mature smooth muscle. Glomus tumors may occur in deep-seated, visceral locations throughout the body, including the lung, pancreas, liver, and gastrointestinal and genitourinary tract [3]. Here, we report the clinicopathologic and immunohistochemical features of gastric glomus tumors (GGTs) seen in two institutions, with the aim of achieving a better understanding of this rare tumor and providing a reference for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The etiology of the glomus tumors remains unclear; however, familial glomus tumors found to have an autosomal dominant pattern with incomplete penetration. 13 Yoo et al 14 reported a case of double glomus tumors in the submandibular and parotid regions. Sixty percent of patients with multiple glomus tumors have had a positive family history, supporting the concept that this abnormality is an inherited disease.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple glomus tumor is a rare benign neoplasm that arises from the glomus body in the stratum reticularis of the dermis, the highly specialized arteriovenous anastomosis for thermoregulation. 1 , 2 , 3 , 4 Although several cases of multiple glomus tumor involving the anterior thigh, 5 submandibular and parotid regions, 6 the torso, 7 have been reported, radiological characteristics on MRI images for multiple glomus tumor have not been described. We reported here both pre-operative and post-operative MR images from a case of 16 years old girl with multiple glomus tumor that partially coalesced on the anterior side of the leg.…”
mentioning
confidence: 99%